The Symmetrical and Asymmetrical Relationship of Technology Acceptance Model (TAM) on Consumer Emotional Value, and Service Innovation in Supporting Consumer Purchase Decisions - Nurlina, Nurliina; Putra, Aditya Halim Perdana Kusuma (International Journal of Artificial Intelligence Research, 2022)
This study aims to determine the symmetrical and asymmetrical relationships between technology, acceptance model (TAM), and consumer emotional value and service innovation in supporting consumer purchase decisions. This research approach uses quantitative research. The primary data sources used in this study are preliminary data obtained from questionnaires and secondary data. This research was conducted in the city of Makassar. The population in this study is based on the infinite population, with a sample of 231 respondents spread across various provinces in Indonesia. Data analysis used validity, reliability, R-square, F-square, direct effect, and partial least square (PLS) hypothesis submission. The results of this study indicate that the Technology Acceptance Model (TAM) variable has a positive and significant effect on the Emotional Value and Service Innovation variables. Likewise, the Technology Acceptance Model (TAM) variable positively and significantly impacts the Consumer Purchase Decision variable by making the Emotional Value variable and Service Innovation intervene. The results of this study also show that the Technology Acceptance Model (TAM) variable has no positive and insignificant effect on the Consumer Purchase Decision variable.